Costimulatory Molecules OX40 and OX40L Upregulation in Oral Squamous Cell Carcinoma: A Blood-Based Study - Sani, Aliya Irshad; Rubab, Zila; Usman, Shumaila; Ahmed, Syed Zaryab; Arif, Sadia (European Journal of Dentistry, 2023)
Objectives This research aimed to determine OX40 and OX40L mRNA expression in blood samples of naive oral squamous cell carcinoma (OSCC) patients in different histological grades and clinical stages. The in silico analysis was performed using the STRING database for functional association and a better understanding of the interactions of OX40 and its ligand with other proteins.Materials and Methods In this study, we recruited 141 newly diagnosed patients of OSCC. Levels of OX40 and OX40L mRNA expression were explored using real-time quantitative polymerase chain reaction. An in silico tool was also utilized to evaluate the OX40/OX40L interactome.Results The results showed higher OX40 expressional levels in the late stage (23-fold) compared with the early stage (8.5-fold) (p = < 0.001). A similar trend was seen in OX40L mRNA expression, revealing a fold change of 5.8 in the early stage in comparison to 9.9-fold change in the late stage (p = < 0.001). Overexpression of OX40 and OX40L was found in different histological grades (p = 0.005 and p = < 0.001, respectively). Overexpression of OX40 and OX40L was detected in habits such as smoking and paan intake, whereas statistically significant upregulation was observed in the cheek, lip, and alveolus tumors. However, there was no substantial difference in OX40 and OX40L expression based on age or gender. The functional interactions, that is, interactomes of OX40 and OX40L with other proteins have been determined by in silico analysis.Conclusion Based on current study findings, despite OX40 and OX40L upregulation in newly diagnosed OSCC patients, it is speculated that the physiological function of these molecules is altered due to immune system exhaustion.
Keywords: OX40; OX40L; immunotherapy; oral squamous cell carcinoma; costimulatory molecules